Twenty-four-hour blood pressure and CSF biomarkers of Alzheimer’s disease and related dementias in a community cohort - Madeline Gibson; William T. O’Brien; Ella Rowsthorn; Katherine H. Franks; Lachlan Cribb; Marina Cavuoto; Beaudan Campbell-Brown; Ian Harding; Meng Law; Trevor T.-J. Chong; Stuart J. McDonald; Terence J. O’Brien; et al. (GeroScience, 2026)
Hypertension in midlife is associated with increased dementia risk, yet its relationship with early pathological changes of Alzheimer’s disease and related dementias (ADRD) remains unclear. Unlike office blood pressure (BP), 24-h ambulatory BP (ABPM) may better reflect cardiovascular risk, but associations between 24-h BP measures with ADRD biomarkers are unknown. This cross-sectional study examined associations between BP and cerebrospinal fluid biomarkers of ADRD in mid-to-late life. Dementia-free participants ( n = 77; mean age = 67 [SD, 6]; 39% women) from the community-based Brain and Cognitive Health (BACH) cohort underwent office and 24-h ABPM assessments to calculate mean BP, nocturnal dipping, blood pressure variability (BPV, coefficient of variation) across 24-h, awake and asleep periods. Participants also completed a lumbar puncture to assess ADRD biomarkers: Aβ42/Aβ40 ratio, phosphorylated tau at threonine 217 (pTau217), glial fibrillary acidic protein (GFAP), and neurofilament light chain (NfL). Linear regression models examined associations between BP and ADRD biomarkers, adjusting for age, sex, BMI, smoking, anti-hypertensive medication use, and APOE ε4 status. Higher 24-h and awake mean BP were associated with higher GFAP (24-h: per 1-SD unit increase, β = 1606.6 pg/mL, p = .03; awake: β = 1668.pg/mL, p = .03) and NfL (24-h: β = 172.3 pg/mL, p = .03; awake: β = 162.3 pg/mL, p = .04) levels. Elevated asleep BPV was associated with higher Aβ42/Aβ40 ratio ( β = 0.01, p = .01). No, other clear associations were identified for the other BP metrics ( p > .05 for all). Findings indicate that elevated BP is associated with neuronal injury and astrocytic reactivity, suggesting possible pathways through which BP may relate to neurodegenerative processes, independent of overt amyloid or tau.

Molecular epidemiology and evolution of norovirus in Australia and New Zealand, 2018 to 2020 - Grace J. H. Yan; Joanne Hewitt; Lewis K. Mercer; Emma F. Harding; Dawn Croucher; Alice G. Russo; Peter G. Huntington; Jason M. Mackenzie; William D. Rawlinson; Peter A. White (Infectious Diseases, 2025)

Factor analysis of multimodal MRI, biofluid, and vascular biomarkers reveals latent constructs of brain health - Ella Rowsthorn; Ming Ann Sim; William T. O’Brien; Stuart J. McDonald; Katherine Franks; Benjamin Sinclair; Trevor T.-J. Chong; Stephanie Yiallourou; Marina Cavuoto; Lucy Vivash; Terence J. O’Brien; Xingfeng Shao; et al. (GeroScience, 2025)
Individual imaging and fluid biomarkers provide insights into specific components of brain health, but integrated multimodal approaches are necessary to capture the complex, interrelated biological systems that contribute to brain homeostasis and neurodegenerative disease. Using data from the Brain and Cognitive Health (BACH) cohort study ( N = 127; mean age = 67 years, 68% women), we performed an exploratory factor analysis to identify latent constructs of brain health. We included multimodal neurovascular imaging markers, brain atrophy metrics, plasma Alzheimer’s disease (AD) biomarkers, and cardiovascular risk factors. Five constructs emerged: “Brain & Vascular Health” (greater hippocampal volume, basal ganglia enlarged perivascular spaces (ePVS), cerebral blood flow, and HDL cholesterol; lower ventricle volume and BMI), “Structural Integrity” (greater cortical thickness, fractional anisotropy, and basal ganglia ePVS), “White Matter (WM) Fluid Dysregulation” (greater WM ePVS and Free Water), “AD Biomarkers” (higher phosphorylated tau [pTau]181 and pTau217; lower amyloid-beta 42/40 ratio), and “Neuronal Injury” (higher glial fibrillary acidic protein and neurofilament light chain). All constructs were associated with age (β = - 0.70–0.39, p ≤ 0.014), except for WM Fluid Dysregulation ( p > 0.05). Brain and Vascular Health and Structural Integrity (partial r = 0.305, p < 0.001) and AD biomarkers and neuronal injury (partial r = 0.248, p = 0.005) were positively correlated. Only Brain and Vascular Health was associated with global cognition (β = 0.27, SE = 0.13, p = 0.043). These findings provide a data-driven framework for examining distinct constructs underlying vascular health, fluid regulation, and neurodegenerative pathology. We demonstrate the utility of using multiple biomarkers to probe these biological systems, paving the way for future research to explore how these systems change across diverse neurodegenerative conditions. Graphical abstract

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Correction to: MR Imaging in Ataxias: Consensus Recommendations by the Ataxia Global Initiative Working Group on MRI Biomarkers - Gülin Öz; Sirio Cocozza; Pierre-Gilles Henry; Christophe Lenglet; Andreas Deistung; Jennifer Faber; Adam J. Schwarz; Dagmar Timmann; Koene R. A. Van Dijk; Ian H. Harding; Astrid Adarmes-Gómez; Andreas Thieme; et al. (The Cerebellum, 2023)

MR Imaging in Ataxias: Consensus Recommendations by the Ataxia Global Initiative Working Group on MRI Biomarkers - Gülin Öz; Sirio Cocozza; Pierre-Gilles Henry; Christophe Lenglet; Andreas Deistung; Jennifer Faber; Adam J. Schwarz; Dagmar Timmann; Koene R. A. Van Dijk; Ian H. Harding; Astrid Adarmes-Gomez; Andreas Thieme; et al. (The Cerebellum, 2023)
With many viable strategies in the therapeutic pipeline, upcoming clinical trials in hereditary and sporadic degenerative ataxias will benefit from non-invasive MRI biomarkers for patient stratification and the evaluation of therapies. The MRI Biomarkers Working Group of the Ataxia Global Initiative therefore devised guidelines to facilitate harmonized MRI data acquisition in clinical research and trials in ataxias. Recommendations are provided for a basic structural MRI protocol that can be used for clinical care and for an advanced multi-modal MRI protocol relevant for research and trial settings. The advanced protocol consists of modalities with demonstrated utility for tracking brain changes in degenerative ataxias and includes structural MRI, magnetic resonance spectroscopy, diffusion MRI, quantitative susceptibility mapping, and resting-state functional MRI. Acceptable ranges of acquisition parameters are provided to accommodate diverse scanner hardware in research and clinical contexts while maintaining a minimum standard of data quality. Important technical considerations in setting up an advanced multi-modal protocol are outlined, including the order of pulse sequences, and example software packages commonly used for data analysis are provided. Outcome measures most relevant for ataxias are highlighted with use cases from recent ataxia literature. Finally, to facilitate access to the recommendations by the ataxia clinical and research community, examples of datasets collected with the recommended parameters are provided and platform-specific protocols are shared via the Open Science Framework.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Cover Image - Lewis K. Mercer; Emma F. Harding; Grace J. H. Yan; Peter A. White (Journal of Fish Diseases, 2022)

Novel viruses discovered in the transcriptomes of agnathan fish - Lewis K. Mercer; Emma F. Harding; Grace J. H. Yan; Peter A. White (Journal of Fish Diseases, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Comparative Biology of Cycad Pollen, Seed and Tissue - A Plant Conservation Perspective - J. Nadarajan; E. E. Benson; P. Xaba; K. Harding; A. Lindstrom; J. Donaldson; C. E. Seal; D. Kamoga; E. M. G. Agoo; N. Li; E. King; H. W. Pritchard (The Botanical Review, 2018)

Fishes in a changing world: learning from the past to promote sustainability of fish populations - T. A. C. Gordon; H. R. Harding; F. K. Clever; I. K. Davidson; W. Davison; D. W. Montgomery; R. C. Weatherhead; F. M. Windsor; J. D. Armstrong; A. Bardonnet; E. Bergman; J. R. Britton; et al. (Journal of Fish Biology, 2018)
Populations of fishes provide valuable services for billions of people, but face diverse and interacting threats that jeopardize their sustainability. Human population growth and intensifying resource use for food, water, energy and goods are compromising fish populations through a variety of mechanisms, including overfishing, habitat degradation and declines in water quality. The important challenges raised by these issues have been recognized and have led to considerable advances over past decades in managing and mitigating threats to fishes worldwide. In this review, we identify the major threats faced by fish populations alongside recent advances that are helping to address these issues. There are very significant efforts worldwide directed towards ensuring a sustainable future for the world's fishes and fisheries and those who rely on them. Although considerable challenges remain, by drawing attention to successful mitigation of threats to fish and fisheries we hope to provide the encouragement and direction that will allow these challenges to be overcome in the future.

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Long-Term Trends of Nutrients and Phytoplankton in Chesapeake Bay - L. W. Harding; C. L. Gallegos; E. S. Perry; W. D. Miller; J. E. Adolf; M. E. Mallonee; H. W. Paerl (Estuaries and Coasts, 2016)

Stability Analysis of Coupled Heat and Mass Transfer Boundary Layers During Steam–Solvent Oil Recovery Process - M. Rabiei Faradonbeh; T. G. Harding; J. Abedi; H. Hassanzadeh (Transport in Porous Media, 2015)

Incidence and distribution of viruses of Taro ( Colocasia esculenta ) in Pacific Island countries - P. A. Revill; G. V. H. Jackson; G. J. Hafner; I. Yang; M. K. Maino; M. L. Dowling; L. C. Devitt; J. L. Dale; R. M. Harding (Australasian Plant Pathology, 2005)

Ultracentrifugation studies on the transmembrane domain of the human erythrocyte anion transporter Band 3 in the detergent C 12 E 8 - H. Cölfen; J. M. Boulter; Stephen E. Harding; Anthony Watts (European Biophysics Journal, 1998)

Quantitative analysis of correlations among flower traits in Gerbera hybrida, Compositae. III. Genetic variability and structure of principal component traits - H. Huang; J. Harding (Theoretical and Applied Genetics, 1998)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Mapping of the gene encoding the B56β subunit of protein phosphatase 2A (PPP2R5B) to a 0.5-Mb region of chromosome 11q13 and its exclusion as a candidate gene for multiple endocrine neoplasia type 1 (MEN1) - S. A. Forbes; A. A. J. Pannett; J. H. D. Bassett; B. Harding; C. Wooding; R. V. Thakker; R. Butler; D. Ogilvie; R. Anand; P. Gaudray; G. Weber; C. Larsson; et al. (Human Genetics, 1997)

Characterisation of the low affinity interaction between rat cell adhesion molecules CD2 and CD48 by analytical ultracentrifugation - H. Silkowski; S. J. Davis; A. Neil Barclay; Arthur J. Rowe; Stephen E. Harding; Olwyn Byron (European Biophysics Journal, 1997)

Low temperature solution behaviour of Methylophilus methylotrophus electron transferring flavoprotein: a study by analytical ultracentrifugation - H. Cölfen; S. E. Harding; Emma K. Wilson; Nigel S. Scrutton; Donald J. Winzor (European Biophysics Journal, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Handwipe sampling and analysis procedure for the measurement of dermal contact with pesticides - P. W. Geno; D. E. Camann; H. J. Harding; K. Villalobos; R. G. Lewis (Archives of Environmental Contamination and Toxicology, 1996)

Handwipe Sampling and Analysis Procedure for the Measurement of Dermal Contact with Pesticides - P. W. Geno; D. E. Camann; H. J. Harding; K. Villalobos (Archives of Environmental Contamination and Toxicology, 1996)